Severe complications of posterior ankle arthroscopy - Dias, Celso Garreta Prats; Mansur, Nacime Salomão Barbachan; Asaumi, Inácio Diogo; Lemos, Andre Vitor Kerber Cavalcanti; Azevedo, Rafael Mohriak; Nery, Caio Augusto de Souza (Scientific Journal of the Foot & Ankle, 2019)
Posterior ankle and hindfoot arthroscopic procedures are associated with a series of possible complications that must be taken into consideration by physicians when performing surgery. This article intends to assess the severe complications, such as subtalar ankle arthrodesis, occurring in patients undergoing ankle arthroscopy procedures in which at least one posterior portal is used. A series of five consecutive patients undergoing posterior ankle arthroscopy-related procedures were assessed. All the complications described in this article were considered severe by the group. We suggest that extreme care is necessary for the training and indications of this very useful but underestimated and complex tool. Level of Evidence V; Therapeutic Studies; Expert Opinion.